Proposed model of case based learning for training undergraduate medical student in surgery - Jamkar, A. V. (Springer-Verlag, 2008)
BACKGROUND: Systematic surveys of undergraduate medical education have cautiously supported the outcomes of Problem Based Learning (PBL) compared with traditional learning. This article provides a critical overview of PBL, its limitations in the developing country scenario and our proposed model of PBL triggered by Real cases, to address these limitations. AIM: Our hypothesis was to see whether the proposed CBL model would work in Indian set up in comparison with traditional teaching METHODS: We followed a modified Barrow’s Model. A tutor selected a real case and created a problem scenario which was progressively disclosed to students, and learning issues were raised. In session 2 students presented self studied learning issues. The process was evaluated throughout with feedback from students and faculty. RESULTS: We were successful in establishing CBL. Study group (n=57) students scored better in SAQ((short Answer question) and EMQ((extended matching question)) assessment, (Mean study 21.15+/− 4.0565, control 18.5357+/−3.8632, n=56, p value 0.01.) Students appreciated it as good learning activity STATISTICAL DESIGN: SAQ and EMQ, are compared in study vs. control groups by unpaired ‘t’ test & also by equivalent non-parametric Mann-Whitney test CONCLUSION: The training of doctors is too important an activity for bold experiments to be conducted without discovery what really happens. We had success in establishing Case based learning with faculty of almost all departments participating in the project as Resources. Although size of sample is small, CBL is found to be an effective modality of imparting medical education with effective integration of all departments.